Changes in circadian rhythm for mRNA expression of melatonin 1A and 1B receptors in the hypothalamus under a neuropathic pain‐like state. Issue 4 (16th January 2014) - Odo, Masahiko; Koh, Keito; Takada, Tomohiko; Yamashita, Akira; Narita, Michiko; Kuzumaki, Naoko; Ikegami, Daigo; Sakai, Hiroyasu; Iseki, Masako; Inada, Eiichi; Narita, Minoru
ABSTRACT Several clinical reports on neuropathic pain of various etiologies have shown that it significantly interferes with sleep. Inadequate sleep due to neuropathic pain may contribute to the stressful negative consequences of living with pain. It is generally recognized that melatonin (MT) system in the hypothalmus is crusial for circadian rhythm and sleep‐wake transition. However, little, if any, is known about whether neuropathic pain could affect the MT system associated with sleep disturbance. In this study, we investigated the possible changes in circadian rhythm for the expression of MT receptors, especially MT1A and MT1B receptors, in the hypothalamus of mice with sciatic nerve ligation. The samples for real‐time RT‐PCR assay were prepared at 8:00, 14:00, 20:00, and 2:00 on day 7 after sciatic nerve ligation or sham operation. The mRNA expression of MT1A and MT1B receptors at 2:00 in sciatic nerve‐ligated mice, which exhibited thermal hyperalgesia along with an increase in wakefulness and a decrease in nonrapid eye movement sleep, was significantly greater than those in sham‐operated mice, whereas the levels of both MT1A and MT1B receptors at 8:00 in sciatic nerve‐ligated mice were significantly lower than those in sham‐operated mice. These findings suggest that neuropathic pain‐like stimuli lead to sleep disturbance in parallel with changes in circadian rhythm for mRNA expression of MT 1A and 1B receptors in the hypothalamus of mice. Synapse 68:153–158, 2014. © 2014 Wiley Periodicals, Inc.